Pure T3 thyrotoxicosis from a Struma Ovarii characterised by a paradoxical rise in thyroxine on treatment. (13th March 2020) - Prentice, James; Panter, Kate; Attygalle, Ayoma; Ind, Thomas; Prentice, Malcolm
Abstract : Summary: A 33-year-old female presented with a right 11.6 cm ovarian cyst. Routine pre-operative thyroid function tests showed thyroid stimulating hormone (TSH) of less than 0.02 mU/L (0.3–3.05) and a free thyroxine (FT4) of 5.5 pmol/L (10–28.2) suggesting either assay interference, triiodothyronine (T3) ingestion or hypopituitary hypothyroidism. A free triiodothyronine (FT3) level was requested which was high normal 6.9 pmol/L (3.1–8.1). Parallel assays on a different platform were similar but with a raised FT3 of 7.2 pmol/L (3.1–6.8). TSH receptor stimulating antibody (TSHAb) and thyroid peroxidase antibodies (TPO) were negative. Antithyroglobulin antibody (TgAb) was positive at 155.6 IU/mL (0–115). She was clinically euthyroid. Thyroid ultrasound showed a normal sized mildly heterogeneous gland with low blood flow and a solitary 1.5 cm U3 (BTA) nodule with higher blood flow. Thyroid Tc 99m uptake was very low 0.2% (0.6–3.0) with no nodule uptake. These results demonstrated an extrathyroidal source of excessive autonomous T3 production resulting in the low thyroxine (T4). With carbimazole her TSH rose to 11.9 mU/L, FT4 rose to 7.7 pmol/L and FT3 reduced to 3.6 pmol/L. Histological diagnosis was Struma Ovarii. Her TSH, FT4 and FT3 remained normal thereafter. In conclusion, an extrathyroidal source of high T3 secretion was diagnosed using routine thyroid tests and scans. We believe this is the first description of a Struma Ovarii exclusively secreting T3 hormone characterised by the paradoxical rise of a low FT4 to normal with treatment. Two years later she developed non-secreting peritoneal deposits of highly differentiated follicular carcinoma. Learning points: Abnormally low TSH and FT4 levels suggestive of possible T3 ingestion, or less likely, hypopituitary hypothyroidism should always be followed by an assay of FT3. The diagnosis of an extrathyroidal source of T3 can be made using conventional thyroid tests, thyroid ultrasound scanning and technetium thyroid uptake and scan imaging. In a pre-menopausal patient this avoids a radiation dose to the pelvis. Pelvic radioisotope scanning of a suspected Struma Ovarii causing thyrotoxicosis can be reserved for patients whose thyroid function remains abnormal after initial surgery. Carbimazole is effective in the treatment of extrathyroidal autonomous T3 hormone production from a Struma Ovarii. The pathological appearance of a Struma Ovarii is not a guide to its malignancy. Even with a benign appearance they can disseminate to peritoneum, as highly differentiated follicular carcinoma (previously known as peritoneal strumosis). Hyperthyroid secretion by a Struma Ovarii may not be replicated in the metastatic follicular carcinoma in the peritoneum.